Seismic performance of circular recycled aggregate concrete-filled steel tubular columns: FEM modelling and sensitivity analysis. (August 2019) - Xu, J.J.; Chen, Z.P.; Zhao, X.Y.; Demartino, C.; Ozbakkaloglu, T.; Xue, J.Y.
Abstract: Recycled concrete aggregates (RCAs) generated from waste concrete have been recognized as a potential alternative to natural aggregates (NAs) for utilization in structural concrete to reduce the environmental impact and achieve the sustainability of resources in engineering constructions. However, it is well known that the overall performances, such as strength, ductility, energy dissipation, durability, etc., of recycled aggregate concrete (RAC) are slightly lower than those of conventional concrete made by NAs. An innovative structural component, namely RAC-filled steel tube (RACFST), was proposed to improve the deficient properties of RAC by using a steel tube to confine concrete. However, literature at large lacks methods to predict the structural performance of RACFST under seismic-induced actions. To address the scarcity of technical information on modelling the seismic performance of circular RACFST, in this study, a fiber-based FEM model is first proposed and then validated using the available experimental data on the hysteresis loops of these columns. The so-validated numerical model is then used to conduct a complete parametric study to investigate the influence of the key parameters governing the mechanical properties of the RAC and of the steel tube on the hysteretic characteristics of circular RACFST columns. Additionally, the compiled database is used to conduct a grey correlation analysis that aims to establish quantifiable evidence of the parametric sensitivity of the seismic performance of circular RACFST columns. The evaluation results show that the use of the additional water method absorption of RCAs in manufacturing RAC reduces the lateral load capacity of the columns, whereas the opposite occurs when this method is not employed. It is also demonstrated that RCA percentage has a less remarkable effect on the seismic performance of CFST manufactured using RCAs, although this effect should be considered in the seismic assessment. Highlights: A fiber section-based nonlinear finite element model was developed to investigate the seismic behavior of circular RACFST columns. Multi-parametric study was performed to investigate the seismic behavior of circular RACFST columns. A grey correlation analysis was used to evaluate the parametric sensitivity of the seismic behavior of circular RACFST columns. Replacement of conventional concrete with RCA affects the overall seismic behavior of CFST columns only slightly.